Evolution of microstructure, strain and physical properties in oxide nanocomposite films - Chen, Aiping (Nature Publishing Group, 2014)
We, using LSMO:ZnO nanocomposite films as a model system, have studied the effect of film thickness on the physical properties of nanocomposites. It shows that strain, microstructure, as well as magnetoresistance strongly rely on film thickness. The magnetotransport properties have been fitted by a modified parallel connection channel model, which is in agreement with the microstructure evolution as a function of film thickness in nanocomposite films on sapphire substrates. The strain analysis indicates that the variation of physical properties in nanocomposite films on LAO is dominated by strain effect. These results confirm the critical role of film thickness on microstructures, strain states, and functionalities. It further shows that one can use film thickness as a key parameter to design nanocomposites with optimum functionalities.